Indigenous Social Control Preventing Drug Misuse Among Pampang Youth in Digital Era (Universitas Terbuka, 2025)
This study investigated the role of indigenous social control in preventing drug misuse among youth in Pampang Village, an urban indigenous community of the Dayak Kenyah in Samarinda, Indonesia. The research was motivated by increasing concerns over the digital era’s influence, particularly social media on youth behavior and moral disengagement. Using a qualitative descriptive method, data were gathered through interviews with the village head and local officers from the National Narcotics Agency (BNN), as well as field observations within the community. The findings revealed that, despite the exposure of youth to online risks, the Pampang community has sustained a strong internal system of social regulation rooted in customary practices. Regular community gatherings in the Lamin (traditional longhouse), especially during year-end cultural rituals, provide a platform for elders to convey collective advice and reinforce social norms. Additionally, close coordination between traditional leaders and state actors namely the Bintara Pembina Desa (village-based military officer) and Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat (community police officer) enhances early prevention of social deviance. These mechanisms, based on communal shame, moral reinforcement, and solidarity, have effectively safeguarded youth from involvement in drug-related issues. The study concludes that indigenous social control, when aligned with formal institutional support, can serve as a resilient cultural framework for preventing youth delinquency in the digital age.